2010
DOI: 10.3354/ame01424
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between crustacean zooplankton and aquatic bacteria

Abstract: Bacteria and metazoan zooplankton (mainly crustaceans) are often viewed as 2 separate functional groups in the pelagic food webs indirectly linked via nutrient cycling and trophic cascades. Yet a zooplankter's body carries a high abundance of diverse bacteria, often at an equivalent concentration orders of magnitude higher than the ambient bacterial concentration. Zooplankton bodies are organic-rich micro-environments that support fast bacterial growth. Their physical-chemical conditions differ from those in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(174 citation statements)
references
References 137 publications
5
169
0
Order By: Relevance
“…However, in reality Bacteria and zooplankton can be tightly linked with each other Tang et al, 2010) such that zooplankton can directly affect bacterial behavior, growth, and biogeochemical activities (Dattagupta et al, 2009). In our study, we found distinct differences between dominant freeliving and zooplankton-associated microbes, supporting the notion that zooplankton can be viewed as islands supporting distinctive communities in the microbial ocean.…”
Section: Microbial Islands In a Changing Oceansupporting
confidence: 77%
“…However, in reality Bacteria and zooplankton can be tightly linked with each other Tang et al, 2010) such that zooplankton can directly affect bacterial behavior, growth, and biogeochemical activities (Dattagupta et al, 2009). In our study, we found distinct differences between dominant freeliving and zooplankton-associated microbes, supporting the notion that zooplankton can be viewed as islands supporting distinctive communities in the microbial ocean.…”
Section: Microbial Islands In a Changing Oceansupporting
confidence: 77%
“…This behavior allows V. fischeri to colonize the squid's light organ and thus underpins a mutualistic relationship that provides the squid with bioluminescent properties (118). Vibrio furnissii exhibits chemotaxis toward chitinous material (20,21,211), which is suggestive of associations with marine crustaceans, cephalopods, or sinking particles and might consequently result in long-range dispersal by transport on zooplankton (67,189).…”
Section: Chemotaxis and Bacterium-animal Associationsmentioning
confidence: 99%
“…Recently, molecular method-based studies have indicated that bacterial diversity in sediment has been linked with impacts of anthropogenic activities, such as increase of eutrophication and chemical pollution [9][10][11][12][13], changes in species of phytoplankton or zooplankton [14][15][16], and operating a dredging, reclamation, or remediation project [17][18][19][20]. Furthermore, some efforts have been made to study the bacterial community structure dynamics related to mariculture processes.…”
Section: Introductionmentioning
confidence: 99%